Basic arithmetic skills intervention for classes (B.A.S.I.C.): Towards improved arithmetic skills for junior high school mathematics - Villanueva, Kenneth Alex R. (Animo Repository, 2021)
“The greatness of a high tower standing strong lies on its foundations.” A building or any construction being established must have a strong foundation that will serve as its source of strength and stability. A poor and defective foundational structure promises nothing but destruction and harm. On the other hand, having a strong and reliable foundation assures safety and solidity. This study emanated from the observation of the researcher that a huge number of junior high school students still encounter difficulties with basic arithmetic operations. The baseline data utilized by the researcher showed that 52.22% of junior high school students from one division were categorized as non-numerates by the Department of Education. This result was more than just a number, but a reminder that students really need help to better their arithmetic skills. In addition, the COVID-19 global pandemic already caused tremendous changes to the education sector—particularly in limiting face-to-face classes. This scenario added to the challenges in bringing meaningful and relevant learnings to students. Given the problems explained above, the purpose of this research was to design, implement, and evaluate an arithmetic online intervention program that aimed to aid mathematically challenged students. Specifically, the BASIC online intervention program, which was anchored on social constructivism and information process (memory), was developed by the researcher to improve students’ arithmetic conceptual understanding and procedural fluency through math talks and math facts. This developmental mixed-method research was implemented among 20 seventh grade students in a public high school in Angeles City. The researcher conducted a six-week online intervention program with activities that supported scaffolding, practice, and discussions facilitated through various online platforms. The quantitative results, particularly students’ pretest, posttest, and math facts scores, were processed using paired samples t-test and Pearson R correlation methods. The majority of data, which were qualitative results of students’ solution strategies, interview responses, and observations, were treated using thematic analysis. Activities that were geared towards the deepening of students’ conceptual understanding and that allowed them to manipulate numbers and identify relationships between variables were devised to improve their procedural fluency. Math facts activities were also employed to aid their problem-solving skills. Students were exposed to problems that familiarized them with the properties of operations. Moreover, it was revealed that allowing students to spontaneously share their insights without the fear of being humiliated and to use their first language were effective in facilitating math talks. Lastly, online activities which were designed to be fun and engaging stirred students to join in the online intervention. While quite a few problems on E-learning were encountered, the researcher and the students were still able to learn from meaningful online interactions and drills. The importance of utilizing research-based principles and data in designing an intervention was highlighted in the implementation of the BASIC program. This paper challenges the teachers to create intervention activities that develop among students 21st Century skills such as collaboration, critical thinking, and problem solving.